Exploring the validity and reliability of online assessment for conversational, narrative, and expository discourse measures in school-aged children - Burchell, Diana; Bourassa Bédard, Vincent; Boyce, Keara; McLaren, Juliana; Brandeker, Myrto; Squires, Bonita; Kay-Raining Bird, Elizabeth; MacLeod, Andrea; Rezzonico, Stefano; Chen, Xi; Cleave, Pat; , FrEnDS-CAN (Frontiers in Communication, 2022)
The COVID-19 pandemic has created novel challenges in the assessment of children’s speech and language. Collecting valid data is crucial for researchers and clinicians, yet the evidence on how data collection procedures can validly be adapted to an online format is sparse. The urgent need for online assessments has not decreased the barriers that clinicians face during implementation. The current study emerged from the project ‘French/English Discourse Study – Canada’ (FrEnDS-CAN), which focuses on a variety of discourse skills in typically developing monolingual and bilingual school-aged children. The present study describes the adapted procedures and compares the outcomes of online and in-person testing using discourse samples and standardized vocabulary testing for monolingual and bilingual children. For the present analyses, 127 (103 in-person, 24 online) English monolinguals and 78 (53 in-person, 25 online) simultaneous French-English bilinguals from ages 7-12 were studied. Several measures were analyzed : receptive vocabulary, conversational discourse, expository discourse, and narrative discourse. Across these measures, productivity, proficiency, and syntactic complexity were calculated . Bayesian statistics and MANOVAs were run to assess the comparability of the two contexts. This study found that there were no differences across testing contexts for receptive vocabulary or narrative discourse. However, some differences were found for conversational and expository discourse. The results from the study contribute to understanding how clinical assessment can be adapted for online format in school-aged children.